The influence of physical activity on the mental health of high school students: the chain mediating effects of social support and self-esteem - Huige Li; Fang Hao (Scientific Reports)
Abstract Mental health issues among high school students have become increasingly prominent. While physical activity is recognized for its ability to reduce symptoms of anxiety and depression, the underlying psychological mechanisms of this effect remain unclear. Social support and self-esteem, as key psychological resources, may mediate the relationship between physical activity and mental health. The aim of this research is to investigate the connection between physical activity and mental health among high school students with an emphasis on the mediating roles of social support and self-esteem. A random sample of 484 high school students (309 males and 175 females) was chosen to take part in an online survey. The survey utilized the PARS-3, the MSPSS, the RSES, the Adolescent Self-Rating Scale (Depression Dimension), and the SWLS. SPSS Statistics 26 with the PROCESS 4.0 macro was used to examine the chain mediation model. Physical activity was significantly positively correlated with life satisfaction and significantly negatively correlated with depression. Physical activity indirectly influenced mental health through social support or self-esteem, and this effect was further enhanced through the chain mediating roles of both factors (life satisfaction: β = 0.0023, SE = 0.0011, 95% CI [0.0002, 0.0047]; depression: β = − 0.0022, SE = 0.0005, 95% CI [− 0.0032, − 0.0014]). The findings emphasize the critical role of social support and self-esteem in the connection between physical activity and mental health. Improving social support and self-esteem can effectively increase the positive impact of physical activity. The findings provide valuable insights for designing more effective mental health interventions for high school students.